THE INFLUENCE OF PRODUCT QUALITY, PRICE AND SOCIAL MEDIA ADVERTISING ON PURCHASE INTEREST IN TIKTOK SHOP E-COMMERCE (STUDY OF STUDENTS OF THE FACULTY OF ISLAM, MUHAMMADIYAH UNIVERSITY OF NORTH SUMATRA): PENGARUH KUALITAS PRODUK, HARGA DAN IKLAN MEDIA SOSIAL TERHADAP MINAT BELI DI E-COMMERCE TIKTOK SHOP (STUDI PADA MAHASISWA FAKULTAS AGAMA ISLAM UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA) - Fitria Anggraini, Wahyu; Tri Adisti Nst, Indah; Fardha Lubis , Nadya (UPMI Proceeding Series, 2023)
This study aims to find out and analyze how much influence product quality has on customer satisfaction, with the TikTok Shop. The results obtained indicate that there is a strong and positive relationship between product quality and customer satisfaction. Quality products have an important role to form customer satisfaction. The higher the quality of the product provided, the higher the satisfaction felt by customers. When customer satisfaction is higher, it can generate profits for the company. Thus, the hypothesis in this study is accepted. Based on the conclusions obtained, it is suggested that customers can choose products offered that are of high quality and in accordance with their needs, desires and expectations so that they are absolutely sure to use these products so they are not disappointed after purchase.